Gandharva and Their Livelihood in Baglung District, Nepal - Panta, Saroj Raj (Dhaulagiri Journal of Sociology and Anthropology, 2021)
This paper focuses on the changing livelihood of the Gandharva, a minority people of Baglung District, Nepal. This research adopts qualitative data based on observations, case studies, in-depth-interview, and a literature review. The data have been thematically analyzed and interpreted. Gandharva usually follow their traditional methods of singing and storytelling (Gainegeet), playing sarangi. Sarangi is a traditional musical instrument. Today many of them have adopted agriculture, carpentry, mason, driving, and labor jobs for their livelihood. They are forced to change their livelihood due to limited income insufficient to fulfill their basic needs. Switching to other occupations is not easy. They face lots of difficulty. Due to globalization and modernization, modern songs, radio, television, you tube, social media are getting popular than songs of Gandharva. People today rarely listen to Gandharva’s songs and Sarangi, which is on the verge of extinction. This paper explores their lives closely to understand their difficulties and struggle for survival.